School Activities that Employ ICT as a Resource to Facilitate Learning in a Student with ADHD - Domínguez, María Alejandra (2019)
This work presents the results of a case study in which professionals work in collaboration to help a student with attention deficit with hyperactivity disorder (ADHD) learn physics. Two kinds of activities were analyzed: activities that include simulations and traditional ones. The attention span of the student in both kinds of activities was compared; in activities that include simulations this span was longer and the disruptive actions were less frequent. Due to this information, the use of simulations in physics learning activities oriented to students with ADHD proves revealing.